2006
DOI: 10.1002/ijc.22201
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary exposure to fiber during pregnancy and mammary tumorigenesis among rat offspring

Abstract: Maternal diet during pregnancy has been proposed to modify female offspring's later susceptibility to develop breast cancer; however, most of the dietary factors identified thus far have led to increased risk. To identify dietary factors that might reduce offspring's breast cancer risk, pregnant rat dams were fed diets containing 6% fiber originating either from cellulose (control), or oat, whole wheat or defatted flax flour. At birth, dams were switched to the AIN93 semi-purified diet. Mammary tumor incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
13
0
3
Order By: Relevance
“…In humans, breast cancer risk is elevated in women who had a high birth weight (12)(13)(14). Animal studies have shown that maternal dietary exposures to a high fat diet (15) or genistein (16) increase, while whole wheat flour (17) or n-3 PUFA (18) reduce female offspring's later mammary tumorigenesis. Maternal dietary exposures during lactation (19) also modify offspring's breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, breast cancer risk is elevated in women who had a high birth weight (12)(13)(14). Animal studies have shown that maternal dietary exposures to a high fat diet (15) or genistein (16) increase, while whole wheat flour (17) or n-3 PUFA (18) reduce female offspring's later mammary tumorigenesis. Maternal dietary exposures during lactation (19) also modify offspring's breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal dietary intake of excess fat or other dietary factors during pregnancy have been shown to affect female offspring's later susceptibility to develop mammary cancer in rats (10)(11)(12). This increase in risk is thought to occur due to an increase in fetal estrogenic environment caused by the maternal diet (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Results from animal studies suggest that maternal dietary or hormonal exposures during pregnancy may have longlasting effects on mammary tumorigenesis among the female offspring (9)(10)(11)(12). For example, maternal exposure to a high-fat diet during pregnancy increases a female offspring's susceptibility to develop carcinogen-induced mammary tumors in rats (9,13), whereas whole wheat flour, containing lignans, and fish oil reduces the risk (10,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excess of fiber is not recommended because it causes nutrient loss and diarrhea during pregnancy. Fiber is effective in prevention of many GI diseases and cancer (11). Fiber rich diet gives optimal calorie control and early satiety in weight loss plans.…”
Section: Dear Editormentioning
confidence: 99%